Harnessing the forces of urban expansion: The public economics of farmland development allowance - Nancy H. Chau; Weiwen Zhang (University of Bonn, Center for Development Research (ZEF), 2011)
For decades, rapid urban expansion has led to concerns over the loss of cultivated land in rural China. This contrasts sharply with another salient feature of the Chinese land policy reform landscape that has gone on largely unnoticed - the addition of newly cultivated land in China through land development has consistently exceeded land conversion. In a model featuring fiscal decentralization, local governments as custodians of land use and development, along with a land development allowance policy instituted in 1998, we show that a land development allowance policy can harness the forces of urban expansion to encourage agricultural land development.
Keywords: H11; H77; P35; R5; R14; O18; 330; land development allowance; fiscal decentralization; inter-jurisdictional competition; agricultural development; Urbanisierung; Bodenverbesserung; Bodenreform; Finanzföderalismus; Theorie; China